Perilaku Hidup Bersih dan Sehat (PHBS) di TKIT Harapan Bunda Manado - Iman, Dian Pratiwi (Indonesian Journal of Early Childhood Education (IJECE), 2024)
Abstract Clean and Healthy Living Behavior, also known as Perilaku Hidup Bersih Sehat (PHBS), represents behaviors based on awareness and learning outcomes, enabling individuals, families, or communities to be self-sufficient in health and actively contribute to public health realization. Early childhood learning should address potential health issues as an initial step to support gradual development and cultivate a generation with solid immune resilience. This research employs a qualitative approach to understand the implementation of clean and healthy living behaviors applied to TKIT Harapan Bunda Kindergarten students as efforts towards achieving a degree of health. The results revealed that clean and healthy living behaviors are already implemented at TKIT Harapan Bunda Kindergarten Manado. Students routinely wash their hands using soap. Students have also developed a habit of disposing of trash properly. In addition, the school offers physical activity once a week and conducts weight and height measurements monthly, along with routine health checks by the Bengkol Health Center. All students generally use the school's toilet facilities for urination and defecation. The school also offers a lunch program with a healthy catering concept called "si Panda." Keywords: Clean and Healthy Living Behavior, Health, Early Childhood